A Study on Linking Korean Wave and Corporate Image on Country Image, Perceived Quality: A Study of China - 김상묵; 김주남; 박민재 (아시아마케팅저널, 2018)
This study examines the linkage between Korean wave, corporate image and country image, perceived quality of products made in the country. To close a gap lacking empirical studies on impacts of corporate image to country image and to further understand impacts of Korean wave, this study conducts survey over Chinese consumers to test the effects of corporate image, Korean wave to the country image, and verify on its effects to perceived quality of the products made in the country. The results show that both corporate image and Korean wave influences to form positive country image of Korea, and perceived quality of Korean made products. The size of effects varies upon products type and stimuli. This study could provide policy makers insights how to promote country image as well as support SMEs for developing overseas markets. Also, it could give marketers valuable implications to develop effective global marketing strategies using cultural assets, country image and salient corporate image.
Keywords: country image; corporate image; Korean wave; perceived quality; popular culture